Atypical neuroimaging in patients with COVID-19 in Peru: case report - Vences, Miguel A. (2020)
Reports describing neurological manifestations in patients with COVID-19 have substantially increased in the past months. Nevertheless, findings from neuroimaging studies have been poorly documented because of restrictions due to the need for isolating such patients. Two cases of patients with COVID-19 and clinical neurological manifestations are reported. They underwent brain imaging studies and atypical findings were made in cerebral magnetic resonance imaging. It is necessary to have more detailed and better documented descriptions of neurological manifestations in patients hospitalized with COVID-19 and their respective neuroimaging correlates in order to obtain better knowledge of this condition.